2017
DOI: 10.1016/j.irfa.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Intraday herding on a cross-border exchange

Abstract: This study investigates intraday herding on the Euronext, the world's first cross-border consolidated exchange. Intraday herding is significant in the Euronext as a group and presents us with size, industry and country effects. Importantly, the trading dynamics of the group's member markets significantly affect each other and can, in the case of the Netherlands, promote herding formation. Intraday herding is found to be significant before, during and after the 2007-09 financial crisis period, with its presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…Our results conform with the findings of Dehghani and Sapian (2014) study where consumer sector stocks were not found to herd. On the other hand, Akbar et al (2019) and Andrikopoulos et al (2017) find significant herding within this industry. The presence of herding impacts the cost of raising new capital in the financial market, thereby impacting the investments and causing asset mispricing.…”
Section: Empirical Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our results conform with the findings of Dehghani and Sapian (2014) study where consumer sector stocks were not found to herd. On the other hand, Akbar et al (2019) and Andrikopoulos et al (2017) find significant herding within this industry. The presence of herding impacts the cost of raising new capital in the financial market, thereby impacting the investments and causing asset mispricing.…”
Section: Empirical Results and Discussionmentioning
confidence: 95%
“…Agriculture, food manufacturing, footwear production, and fuel processing also display herd pattern in the Chinese equity markets (Shah, Khan, Meyer, Meyer,& Oláh, 2019). The research on European countries using high frequency sample period data also report herding for sectors such as consumer goods, industrial and utilities, and healthcare (Andrikopoulos, Kallinterakis, Ferreira,& Verousis, 2017). In contrast, the Australian equity market does not engage in herd mentality at the aggregate or industry level (Henker, Henker,& Mitsios, 2006).…”
Section: Studies On Herding At Sector Levelmentioning
confidence: 99%
“…We then explore whether our results are driven by the size effect, a well-known determinant of institutional herding internationally (Andrikopoulos et al, 2017). To that end, we rank the universe of stocks that our sample funds have invested in each year into five quintiles (Q1 to Q5, with Q1 corresponding to the smallest and Q5 to the largest capitalization stocks) based on those stocks' market capitalization 28 at the end of the immediately preceding year and repeat all estimations from Tables 4-7.…”
Section: Robustness Testsmentioning
confidence: 99%
“…In this context, studies on herding behavior surrounding events such as civil unrest are those that consider times of crisis, such as the subprime crisis and the Asian crisis (Andrikopoulos et al, 2017 andOmay &Iren, 2019, respectively). Andrikopoulos et al (2017) consider a sample of Euronext member countries reporting intraday herding behavior before, during and after the period of said financial crisis (2007-09), with its presence being less prominent during the crisis. Omay and Iren (2019) report herding behavior for Malaysia during the Asian crisis for both foreign and domestic investors.…”
Section: Herding Behavior In Financial Marketsmentioning
confidence: 99%
“…In financial markets, one way for investors to overcome periods of crisis is adopting herding behavior (Andrikopoulos et al, 2017;Omay & Iren, 2019). This behavior allows them to imitate the actions of others using the same sources of information and interpreting signals sent to the market in an identical way, and, consequently, making similar financial decisions (Hirshleifer et al, 1994).…”
Section: Introductionmentioning
confidence: 99%